The making, implementation and protection of rights in the Charter of Fundamental Rights of the European Union - Andrzejewski, Piotr (Wielkopolska Rada Młodzieży, 2012)
Artykuł traktuje o mocy obowiązującej Europejskiej Karty Praw Podstawowych. Autor analizuje treść Karty oraz przedstawia możliwości jej zastosowania. Przedmiotem analizy jest również skomplikowany system tworzenia europejskiego prawa, którego dzieckiem był polityczny kompromis jaki stanowi Europejska Karta Praw Podstawowych.

The article covers the issue of the legal power of the Charter of Fundamental Rights of the European Union. The author analyses the content of the Charter and situations in which it can be applied. He also describes the complex world of European legislation that shaped the Charter which was a political compromise.
Keywords: Karta Praw Podstawowych; Europejska Karta Praw Podstawowych